Analysis of Quality of Life Among Covid-19 Survivors in Medan - Ansari, Cindi; Ismah, Zata (Poltekkes Kemenkes Tanjung Karang, 2024)
The Covid-19 pandemic is a global challenge with significant impacts in various countries, including Indonesia. This study investigates the quality of life of Covid-19 survivors in the Medan Sunggal Sub-district, considering age, gender, education, employment status, and disease duration. Descriptive research was conducted from March to June 2023, involving 146 respondents aged 16-55 who had survived for one year. The snowball sampling method was applied, and data were collected using the SF-36 questionnaire. Results showed that early adulthood and female age groups tended to have better quality of life. Higher education was also positively correlated with quality of life. The implications of these findings support the development of specific recovery and support programs for Covid-19 survivors, especially those experiencing prolonged symptoms. With a better understanding of the factors that influence the quality of life of Covid-19 survivors, recommendations include developing rehabilitation and support programs tailored to individual characteristics. These efforts are expected to support optimal recovery and contribution to the response to the pandemic in Medan Sunggal Sub-district.